2021
DOI: 10.3389/fnbeh.2021.610078
|View full text |Cite
|
Sign up to set email alerts
|

Age Impacts the Burden That Reference Memory Imparts on an Increasing Working Memory Load and Modifies Relationships With Cholinergic Activity

Abstract: Rodent aging research often utilizes spatial mazes, such as the water radial-arm-maze (WRAM), to evaluate cognition. The WRAM can simultaneously measure spatial working and reference memory, wherein these two memory types are often represented as orthogonal. There is evidence, however, that these two memory forms yield interference at a high working memory load. The current study systematically evaluated whether the presence of a reference memory component impacts handling of an increasing working memory load.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…We also note here that MWM outcomes are different from the pattern of effects observed for RM outcomes on the WRAM. This coincides with several studies from our laboratory indicating that assessing reference memory in conjunction with working memory differs from assessments of one memory type alone, effects seen in both young and aged females 35 , 40 , 55 .…”
Section: Discussionsupporting
confidence: 91%
“…We also note here that MWM outcomes are different from the pattern of effects observed for RM outcomes on the WRAM. This coincides with several studies from our laboratory indicating that assessing reference memory in conjunction with working memory differs from assessments of one memory type alone, effects seen in both young and aged females 35 , 40 , 55 .…”
Section: Discussionsupporting
confidence: 91%
“…Rats that received E2 plus levonorgestrel treatment also had improved reference memory during task acquisition compared to rats treated with E2 plus progesterone concomitantly, suggesting a unique cognitively beneficial role for levonorgestrel when combined with E2 to enhance learning on a complex spatial working memory task. Reference memory benefits observed for the rats treated with daily E2 plus levonorgestrel treatment did not carry over into MM, indicating that the presence of a working memory component in a task alters outcomes on the reference memory measure, an effect we have previously shown in normally aging, ovary-intact rats without hormone treatment ( Bernaud et al, 2021 ). During the latter portion of WRAM testing, transitionally menopausal rats treated with only progesterone showed working memory impairments when working memory was taxed compared to counterparts without hormone treatment, with levonorgestrel treatment, or with E2 plus progesterone treatment.…”
Section: Discussionmentioning
confidence: 64%
“…Day 1 was considered task acquisition and was not included in the analyses. Based on previous findings from our laboratory, WRAM data were blocked into the Learning Phase (Days 2-8) and the Asymptotic Phase (Days 9-12), as published previously ( Bimonte and Denenberg, 1999 ; Bimonte-Nelson et al., 2003a ; Bimonte-Nelson et al., 2003a ; Bimonte-Nelson et al., 2004 ; Mennenga et al., 2015a ; Braden et al., 2017 ; Koebele et al., 2020a ; Bernaud et al., 2021 ). A priori planned analyses evaluating high working memory load trials (Trial 3 and Trial 4) were also completed, as our laboratory has previously reported age- and hormone- mediated effects when working memory load is sufficiently burdened ( Bimonte and Denenberg, 1999 ; Mennenga et al., 2015a ; Mennenga et al., 2015b ; Koebele et al., 2019 ; Koebele et al., 2020b ).…”
Section: Methodsmentioning
confidence: 99%